Physical and tensile properties of epoxy laminated magnetic bacterial cellulose nanocomposite films. Issue 30 (10th April 2017) - Mashkour, Mahdi; Moradabadi, Zahra; Khazaeian, Abolghasem
ABSTRACT: Despite many potential applications, the adverse impacts of magnetic nanoparticles on the tensile properties of magnetic cellulose papers and films are well established. On the other hand, water absorption and thickness swelling of cellulose materials are important limiting factors in many engineering applications. These challenges caused limited applications of magnetic cellulose nanocomposites. The aim of this study is to examine the possibility of modifying the physical and mechanical behaviors of magnetic bacterial cellulose films by epoxy resin lamination. Results showed that the tensile modulus and strength of the magnetic bacterial cellulose film, respectively, increased about 280% and 240% after epoxy lamination while they maintained their desirable magnetic and flexibility properties. Furthermore, the water absorption and thickness swelling of the epoxy laminated magnetic nanocomposite films, respectively, improved about 43% and 42%. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45118. Abstract :